Filling Defect of Ipsilateral Transverse Sinus in Acute Large Artery Occlusion - Yi Chen (Frontiers in Neurology, 2022)
Background and PurposeCerebral venous systems play a key role in regulating stroke outcomes. We aimed to elucidate the effect of the transverse sinus (TS) filling patterns on edema expansion and neurological outcomes in patients with acute large artery occlusion (LAO).Materials and MethodsWe recruited consecutive patients with acute M1 middle cerebral artery and/or internal carotid artery occlusion who underwent pretreatment computed tomographic perfusion (CTP). On the reconstructed 4-dimensional computed tomographic angiography derived from CTP, the filling defect of the ipsilateral transverse sinus (FDITS) was defined as the length of contrast filling defect occupying at least half of the ipsilateral TS. An unfavorable outcome was defined as having a modified Rankin Scale (mRS) score of 3–6 at 3 months.ResultsA total of 318 patients were enrolled in the final analysis and 70 (22.0%) patients had baseline FDITS. The presence of FDITS was associated with the baseline NIHSS (odds ratio [OR] 1.119; 95% CI, 1.051–1.192; p < 0.001) and poor arterial collaterals (OR 3.665; 95% CI 1.730–7.766; p = 0.001). In addition, FDITS was associated with 24-h brain edema expansion (OR 7.188; 95% CI, 3.095–16.696; p < 0.001) and 3-month unfavorable outcome (OR 8.143; 95% CI 2.547–26.041; p < 0.001) independent of arterial collateral status. In the subgroup analysis of patients with FDITS who received reperfusion therapy, no significant difference was found in the rate of edema expansion and unfavorable outcome between non-reperfusion and reperfusion subgroups (both p > 0.05).ConclusionFilling defect of the ipsilateral transverse sinus was associated with edema expansion and an unfavorable outcome irrespective of the baseline arterial collateral status in patients with acute LAO, indicating that FDITS may be an important stroke-related prognostic imaging marker.